The rhizosphere microbiome improves the adaptive capabilities of plants under high soil cadmium conditions - Fan, Wenjun; Deng, Jinmei; Shao, Li; Jiang, Shiming; Xiao, Tangfu; Sun, Weimin; Xiao, Enzong (Frontiers in Plant Science, 2022)
Cadmium (Cd) contamination of agricultural soils poses a potential public health issue for humans. Phytoremediation-based accumulating plants are an effective and sustainable technology for Cadmium remediation of contaminated agricultural soil. The root microbiome can promote the growth and Cadmium accumulation in hyperaccumulators, but its taxonomic and functional traits remain elusive. The present study used two ecotypes of Sedum alfredii, an accumulating ecotype (AE) and a non-accumulating ecotype (NAE), as model plants to investigate the root microbiome assemblages and influence on plant growth under high cadmium conditions. Our results showed that distinct root microbiomes assembled in association with both ecotypes of Sedum alfredii and that the assemblages were based largely on the lifestyles of the two ecotypes. In addition, we demonstrated that the functions of the microbes inhabiting the rhizosphere soils were closely associated with root-microbe interactions in both ecotypes of Sedum alfredii. Importantly, our results also demonstrated that the root microbiome assembled in the AE rhizosphere soils contributed to plant growth and cadmium uptake under high cadmium conditions through functions such as nitrogen fixation, phosphorus solubilization, indole acetic acid (IAA) synthesis, and siderophore metabolism. However, this phenomenon was not clearly observed in the NAE. Our results suggest that the root microbiome plays important roles in biogeochemical nutrient and metal cycling that can contribute to host plant fitness.